Reliability engineering and risk analysis : a practical guide - Modarres, M. (Mohammad); Kaminskiy, Mark, 1946-; Krivtsov, Vasiliy, 1963- (CRC, CRC Press is an imprint of the Taylor and Francis Group, an informa business/CRC Press,Taylor & Francis Group, 2017)
This undergraduate and graduate textbook provides a practical and comprehensive overview of reliability and risk analysis techniques. Written for engineering students and practicing engineers, the book is multi-disciplinary in scope. The new edition has new topics in classical confidence interval estimation; Bayesian uncertainty analysis; models for physics-of-failure approach to life estimation; extended discussions on the generalized renewal process and optimal maintenance; and further modifications, updates, and discussions. The book includes examples to clarify technical subjects and many end of chapter exercises. PowerPoint slides and a Solutions Manual are also available.